(untitled) (Revista Brasileira Multidisciplinar, 2025)
According to the 2019 National Health Survey (PNS), 2.7% of the Brazilian population over the age of 2 had a physical disability related to the use of their upper limbs. The significant number of users, coupled with advances in research in the field of Assistive Technology (AT), has stimulated research for the development of prostheses. This paper presents the development of a low-cost, mechanically actuated active prosthesis consisting of a purely mechanical actuation mechanism. The prosthesis structure was developed by improving a model available on the GRABCAD COMMUNITY platform and manufactured using FDM (Fused Deposition Modeling) additive manufacturing, and the product’s characteristics were selected through a morphological matrix. The user’s stump movements (part or all of the carpus) are used to actuate the fingers and consequently perform basic prosthesis movements, such as pinch and grasp movements.